Information workflow proposal for integrating cost estimating, scheduling, and monitoring with BIM in SMEs - Santos, Mírian Caroline Farias (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2021)
Although many studies have emphasized the benefits of the integration of Building Information Modeling (BIM), there is no consensus on the information workflow among main processes used in construction, particularly in small- and medium-size enterprises (SMEs). Therefore, this work proposes an information workflow that integrates 3D BIM modeling, cost estimating, scheduling, and monitoring processes in SMEs (ICSM Information Workflow). This research adopts the design science research approach, which includes (a) a literature review and a study of the information workflow among the processes, (b) a proposal of an information workflow based on certain assumptions for integration, (c) a participatory process for testing and adapting the proposed workflow, and (d) an evaluation of the proposed information workflow. The results indicate the participatory and cyclical processes that were proposed to define the work packages using a standard WBS and a database for information integration were the key for integrating people, technologies, and processes. The main contributions of this study are the proposal of an information workflow that integrates cost estimating, scheduling, and monitoring with BIM in SMEs, and the lessons learned based on the pilot test and evaluation of the ICSM Information Workflow in one of the two projects studied.